Postharvest conservation of 'Tommy Atkins' mango fruit influenced by gamma radiation, wax, hot water, and refrigeration - Durigan, José Fernando [UNESP]; De Almeida Teixeira, Gustavo Henrique [UNESP]; Castanharo, Nivaldo Marcos [UNESP]; Domarco, Rachel Elizabeth [UNESP] (My University, 2004)
It was aimed to extend the postharvest conservation of 'Tommy Atkins' mango fruits harvested in break maturity stage. Fruits were submitted at the following treatments: hot water treatment (55°C for 5 minutes) and benomyl 1,000 mg.L-1; irradiation with 0,8 or 1,0 kGy; irradiation associated at carnaúba wax; and control. The fruits were stored at 10°C and 85 - 90%RH during 21 days, and then removed to ambient temperature (25,7±0,7°C and 87,1±2,2%RH). Through the storage time, the evolution of fresh weight, color, rottenness, total soluble solids (TSS), total titratable acidity (TTA), and TSS/TTA ratio were measured. 'Tommy Atkins' mango fruits can have shelf life notably increased, when they were submitted to hot water treatment (55°C for 5 minutes) or γ radiation (0,8 and 1,0 kGy), associated with carnaúba wax application, before cold storage. These treatments increased the fruit resistance at refrigerated storage, and improved shelflife after transferring to ambient temperature.
Keywords: Anthracnose; Colletotrichum gloeosporioides; Decay; Physiology; Postharvest